Monitoring dan Evaluasi Perubahan Penggunaan Lahan Berbasis Penginderaan Jauh di Kecamatan Klungkung, Kabupaten Klungkung - Astika, I Komang Putra; Diara, I Wayan; Bhayunagiri, Ida Bagus Putu (Agrotrop : Journal on Agriculture Science; Vol 13 No 3 (2023)DO - 10.24843/AJoAS.2023.v13.i03.p06, 2023)
Monitoring and Evaluation of Landuse Changes based on Remote Sensing in Klungkung District, Klungkung Regency. Bali Province is one of the tourism destinations in Indonesia, the tourist destinations, offered include beauty of nature, art, culture traditions, and historical buildings one of them is in the Klungkung District such as Kertagosa, Gunarsa Museum the Klungkung Monument.  Klungkung District has a large population that a 65,273 people, which can changes in landuse, therefore the research about monitoring and evaluation of landuse change in Klungkung district is needed. The purposes of this research are to determine landuse changes in Klungkung District, the level of accuracy of the classification result of Landsat imagery in 2022, and the relation between classified land use map and spatial planning of Klungkung Regency. The method which is used in this research is the maksimum likehood classification (MLC) in the land use supervised classification. Digital classification for landuse landcover were analyst using semi-automatic classification plugin (SCP) in QGIS 3.22 LTR Apps. The result shows that, it was found that built-up land has a regularity of change of 28,155 ha/yr, rice fields with a regularity of change of 50.5 ha/yr, bare land with an area of 16.88 ha/yr, and dryland farming with a regularity of change reaching 61.7 ha/yr. The overall accuracy of this research was 82.42 % and a kappa index 0.75. The overlay by spatial planning was found that there was a discrepancy the land use in 2022.